Morfologi Arsitektur Dan Transformasi Fisik Masjid Agung Lamongan - Hammam Rofiqi Agustapraja; Yulistia Maulidina (Jurnal Teknika, 2019)
The Great Mosque of Lamongan as a cultural asset in Lamongan has experienced many developments, expansions, and changes in physical form, especially in the facade which is the outward appearance of a building. In this study, there are problems with the morphological approach and physical transformation in the Great Mosque of Lamongan based on the incorporation of a typology of the facade into new formations ?. The method in this study with descriptive analysis in the manifestation of the change in the form of the Lamongan Great Mosque facade from time to time, then the approach used is a historical approach. From this approach, the physical changes are analyzed according to the style (typology) of the existing Mosque Architecture typology. The results of this study state that the merging of forms between the characteristics of universality and locality results in a dynamic formation with local characteristics